From Theory to Practice: Teachers’ Perspectives and Challenges in Implementing Merdeka Curriculum for Lesson Planning - Elsa, Elsa; Rahim, Titin Rahmiatin; Tohamba, Citra Prasiska Puspita (Journal of English Language and Education, 2024)
This study discusses teachers' experiences in implementing the Merdeka Curriculum, especially in lesson planning and achieving learning objectives. The purpose of this study is to explore the challenges and opportunities faced by teachers in implementing the curriculum. The research used a qualitative approach involving 18 English teachers who have implemented the Merdeka Curriculum for 1-2 years, with data collection through questionnaires and interviews adapted by previous research. The results showed that although many teachers experienced difficulties in designing flexible lesson plans, they saw this curriculum as an opportunity to increase students' creativity and independence. This research provides insight into the challenges teachers face in achieving effective learning outcomes.